Neonate Brain Abscess by Cronobacter spp: A Powdered Infant Formula's Opportunistic Pathogen - Morais, Bárbara Albuquerque; Menendez, Djalma Felipe Da Silva; Ribeiro, Iuri Santana Neville; Borsetto, Cibeli Ribeiro; Nascimento, Fernando De Sousa; Teixeira, Manoel Jacobsen (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Cronobacter spp is an opportunistic pathogen that can cause severe neonatal infections, including septicemia, meningitis, and necrotizing enterocolitis. Over 90% of these infections outbreaks are associated with the increased consumption of powdered infant formula (PIF). We report the case of a male neonate born at term with adequate weight for gestational age, fed by breast milk and PIF. He was admitted to the ICU at 22 days old due to fever, irritability, impaired consciousness, and food intolerance. Investigation revealed an extensive abscess in the right frontoparietal region, that was surgically drained. The culture of the purulent material showed the growth of Cronobacter spp. Guided antibiotic was kept for 21 days. The patient presented a good clinical outcome, without neurological deficits. The microbiological powdered formula contamination by Enterobacter sakazakii (Cronobacter spp) can lead to a higher risk of severe infections in infants. Children may present sepsis, sensory alteration, and refractory seizures. An early brain image should be considered for symptomatic infants. The mortality rate ranges from 40 to 80%, and 74% of survivors have an adverse neurological outcome. From 1997–2013, there were reports of 6 outbreaks of E. sakazakii disease in Brazil. According to the World Health Organization (WHO), this disease is undernotified, and active foodborne surveillance systems are less than ideal. To better address this problem, in some countries, the notification is mandatory, and the adoption of stricter sanitary measures by regulatory agencies are proposed.
Keywords: enterobacter sakazakii; cronobacter spp.; brain abscess; powdered infant formula; neonatal sepsis